2019
DOI: 10.1111/jgh.14707
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of direct‐acting agents for hepatitis C and liver stiffness changing after sustained virological response

Abstract: Background and AimFew studies have evaluated sustained virological response (SVR) rates by direct‐acting agents (DAAs) and liver stiffness measurement (LSM) changing post‐SVR in limited‐resource settings. We aimed to describe the effectiveness of DAAs for hepatitis C virus treatment and to assess the changing of LSM post‐SVR.MethodsThis retrospective study analyzed data of consecutive hepatitis C virus‐infected patients treated by DAAs from 2015 to 2017 in two tertiary centers in Brazil. SVR rates were reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 43 publications
4
21
1
Order By: Relevance
“…In our study overall, HCV clearance after DAA therapy promoted a signi cant improvement in severity scores of liver cirrhosis and many plasma biomarkers linked to in ammation (bacterial translocation, in ammatory response, and endothelial dysfunction) and coagulopathy. Our data are in concordance with a large number of previous studies that found a signi cant decrease in liver disease scores of HIV/HCV-coinfected patients [6,7,32,[43][44][45] and HCV-monoinfected patients [6][7][8][9][10][11][12][13][14] after HCV eradiation with DAA therapy; and also in plasma biomarkers of HIV/HCV-coinfected patients [18,[30][31][32][33][34] and HCV-monoinfected patients [15][16][17][18][19][20]. However, there is an important lack of consistency in these previous publications regarding the plasma biomarkers and liver severity scores evaluated, time-points used to take data or samples after the end of HCV treatment, statistical analysis used, and liver brosis stages included.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study overall, HCV clearance after DAA therapy promoted a signi cant improvement in severity scores of liver cirrhosis and many plasma biomarkers linked to in ammation (bacterial translocation, in ammatory response, and endothelial dysfunction) and coagulopathy. Our data are in concordance with a large number of previous studies that found a signi cant decrease in liver disease scores of HIV/HCV-coinfected patients [6,7,32,[43][44][45] and HCV-monoinfected patients [6][7][8][9][10][11][12][13][14] after HCV eradiation with DAA therapy; and also in plasma biomarkers of HIV/HCV-coinfected patients [18,[30][31][32][33][34] and HCV-monoinfected patients [15][16][17][18][19][20]. However, there is an important lack of consistency in these previous publications regarding the plasma biomarkers and liver severity scores evaluated, time-points used to take data or samples after the end of HCV treatment, statistical analysis used, and liver brosis stages included.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, signi cant decreases in liver disease scores [liver stiffness measurement (LSM), hepatic venous pressure gradient (HVPG) or Child-Pugh-Turcotte (CTP)] [6][7][8][9][10][11][12][13][14] and plasma biomarkers related to in ammation and immune activation [15][16][17][18][19][20] have been described in HCV-monoinfected patients after SVR with all-oral DAAs.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence on the effectiveness and safety of DAAs was showed in real-world studies conducted at different settings and subsequent meta-analyses [1,[29][30][31][32][33][34][35][36]. However, to our knowledge, this is the first systematic review and meta-analysis that evaluates the effectiveness of the delivery of HCV treatment with DAAs by non-specialized health personnel at primary care.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes has clearly been described as risk factor for brosis progression in nonalcoholic liver disease patients but its impact on chronic hepatitis C patients has not been prospectively evaluated [15]. Fernandes et al have found a similar impact of diabetes in CHC patients but on a retrospective study that included only SVR patients, without the possibility to compare SVR patients with NR or naïve patients [9]. The prognostic impact of DM observed in our study has great relevance in clinical practice since it might further be the basis to recommend that in daily clinic patients with DM should be kept under care despite virological cure.…”
Section: Discussionmentioning
confidence: 99%
“…So far, most published studies have focused speci cally in the follow-up of SVR patients group [6,8,9,18,20],describing the straight relationship of SVR and improvement of liver brosis with several non-invasive methods like TE and acoustic radiation force impulse. Currently, HCV treatment is effective in most of treated patients, however, assess to treatment is still an issue in many countries, mainly those underdeveloped countries.…”
Section: Discussionmentioning
confidence: 99%